Pengalaman ibu menyusui di RSIA X kota Malang - Fiella Rachmatika; Harun Al Rasyid; Lilik Zuhriyah (Fakultas Kedokteran Universitas Gadjah Mada, 2019)
The experience of breastfeeding mothers in RSIA X MalangPurpose: Several factors cause a low level of exclusive breastfeeding in Indonesia. One of them is breastfeeding, which is not immediately resolved by health workers in the hospital. Mothers who have just given birth in an MCH hospital expect help and assistance from health professionals to not have difficulty breastfeeding. This study is to uncover the experience of nursing mothers in an MCH hospital. Method: This phenomenology research took place in a hospital in Malang in April-May 2019 with five informants by purposive sampling. Data were from in-depth interviews and analyzed using an interpretive phenomenology analysis. Results: There were seven themes: satisfied and comfortable giving birth, health workers in hospitals did not deliver breastfeeding information and assistance, more comfortable breastfeeding because it was practical and economical, grateful to have struggled to provide breastfeeding so that children were healthy, disappointed and worried about breastfeeding, pain, and tiredness of breastfeeding, the desire to obtain breastfeeding support and information from the hospital. The mother expects to obtain breastfeeding support in the form of information and assisting breastfeeding so that the mother understands how to breastfeed and does not experience breastfeeding problems when returning home. Conclusion: Our study hospital did not consistently serve as a friendly environment for breastfeeding mothers.